Presence of negative supercoiling in aggregates of histone H1-plasmidic polynucleosome complexes - Zhang, Hao (2017)
It was shown in the past that in the presence of histone H1, plasmidic polynucleosomes formed densely packed aggregates. Our current studies demonstrate that these aggregates are susceptible to the actions of E. coli topoisomerase I, human topoisomerase I and DNA nicking enzyme, which is the indication that negative supercoiling is present in the condensed DNA-protein complexes. Since negative supercoiling leads to formation of highly curved and compact plectonemic and toroidal DNA structures, it would be reasonable to assume that DNA negative supercoils are responsible for aggregation of histone H1-plasmidic polynucleosome complexes.